Dari Dosen ke Advokat: Telaah Putusan Mahkamah Konstitusi Nomor 150/PUU-XXII/2024 dalam Perspektif Siyasah Qadhaiyyah - Mukhsin Mukhsin; Rahmat Efendy Siregar; T. Surya Reza (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
Civil servant lecturers are required to fulfil the Tri Dharma of Higher Education, including community engagement, which may take the form of providing legal assistance. In practice, this obligation encounters a legal barrier because Article 3 paragraph (1)(c) and Article 20 paragraph (2) of Law Number 18 of 2003 on Advocates prohibit civil servants from practising as advocates. This restriction has triggered debate over whether law lecturers, as civil servants, may exercise their constitutional rights to participate in advocacy work. This study seeks to examine the Constitutional Court’s legal reasoning in Decision Number 150/PUU-XXII/2024, which authorises civil servant lecturers to act as advocates within certain limits, and to assess the relevance of this decision through the lens of siyasah qadhaiyyah. Employing a qualitative research design supported by a statute approach and analytical approach, the study analyses pertinent primary and secondary legal sources. The findings reveal that the Constitutional Court issued a conditionally unconstitutional ruling on the contested provisions of the Advocate Law, clarifying that civil servant lecturers may undertake advocacy activities solely for pro bono services through university legal aid institutions. This ruling affirms the protection of constitutional rights guaranteed in Articles 28C and 28D of the 1945 Constitution and resonates with principles of substantive justice in siyasah qadhaiyyah, particularly the pursuit of the public good (maslahah ammah) through the involvement of legal scholars. The study concludes that constitutional justice and Islamic legal ethics can be synergised to balance individual rights with the professional responsibilities inherent to state officials.